2015
DOI: 10.1557/jmr.2014.384
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy with in situ ion irradiation

Abstract: The macroscopic properties of materials exposed to irradiation are determined by radiation damage effects which occur on the nanoscale. These phenomena are complex dynamic processes in which many competing mechanisms contribute to the evolution of the microstructure and thus to its end-state. In order to explore and understand the behaviour of existing materials and to develop new technologies, it is highly advantageous to be able to observe the microstructural effects of irradiation as they occur.Transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In general, the response of nanostructured materials to radiation damage is still poorly understood [29]. Despite the limited understanding in the general field, freestanding gold nanoparticles (usually drop casted onto carbon or silicon nitride TEM grids) have been used as the model system for testing and validation of TEM with in-situ ion irradiation capabilities [52][53][54]. Expanding on the known enhanced sputtering rates observed in gold thin foils exposed to a range of noble gas ions [55], it was later shown by Ilinov et al that gold nanorods irradiated with 80 keV Xe demonstrated sputtering rates with three orders of magnitude higher than predicted by classical sputtering simulations [27].…”
Section: Radiation Stability Of Freestanding Gold Nanoparticlesmentioning
confidence: 99%
“…In general, the response of nanostructured materials to radiation damage is still poorly understood [29]. Despite the limited understanding in the general field, freestanding gold nanoparticles (usually drop casted onto carbon or silicon nitride TEM grids) have been used as the model system for testing and validation of TEM with in-situ ion irradiation capabilities [52][53][54]. Expanding on the known enhanced sputtering rates observed in gold thin foils exposed to a range of noble gas ions [55], it was later shown by Ilinov et al that gold nanorods irradiated with 80 keV Xe demonstrated sputtering rates with three orders of magnitude higher than predicted by classical sputtering simulations [27].…”
Section: Radiation Stability Of Freestanding Gold Nanoparticlesmentioning
confidence: 99%
“…In general, the response of nanostructured materials to radiation damage is still poorly understood [46]. Despite the limited understanding in the general field, free-standing gold nanoparticles (usually drop-cast onto carbon or SiN TEM grids) have been used as the model system for testing and validation of TEM with in-situ ion irradiation capabilities [47][48][49]. Expanding on the known enhanced sputtering rate observed in gold thin foils exposed to a range of noble gas ions [50], it was later shown by Ilinov et al that gold nanorods irradiated with 80 keV Xe demonstrated sputtering rates three orders of magnitude higher than those predicted by classical sputtering simulations [33].…”
Section: Literature Surveymentioning
confidence: 99%
“…New capabilities in in-situ ion irradiation allow for direct observation of He bubble nucleation and growth as a function of He implantation dose and temperature [10]. In the new Microscope and Ion Accelerators for Materials Investigations (MIAMI-2) facility at the University of Huddersfield [11], in-situ He implantation has been combined with Environmental Transmission Electron Microscopy (ETEM), which allows for imaging in the presence of milliTorr H 2 pressures.…”
Section: Introductionmentioning
confidence: 99%